2022
DOI: 10.1109/access.2022.3160485
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Static Code Analysis With Language-Agnostic Component Identification

Abstract: Static code analysis of software systems has proven beneficial for a broad range of domains, including security assessments, coding practice, error detection, and others. However, as modern systems have grown in complexity and heterogeneity over the past few decades, advances in development frameworks have dominated. Rather than involving low-level language constructs, these frameworks typically focus on software components, including data entities, controllers, and endpoints. As a result, current code analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…In future work, we plan to perform a large user study for which we have already obtained IRB approval. The SAR process will also be generalized to a platformagnostic approach as initiated in [48]. We will also assess more architectural views and alternative 3D models.…”
Section: Discussionmentioning
confidence: 99%
“…In future work, we plan to perform a large user study for which we have already obtained IRB approval. The SAR process will also be generalized to a platformagnostic approach as initiated in [48]. We will also assess more architectural views and alternative 3D models.…”
Section: Discussionmentioning
confidence: 99%
“…In our research and prototyping[24, 2] 1 and [12] 2 , we focused on microservice middleware, on the detection communication patterns between services [16,20,21] and on metrics to detect coupling based on the interaction between microservices detected with static analsyis [15]. Furthermore, we observed that most microservices would be developed using particular platform frameworks that introduce components [5,18]. Among examples, consider Spring or Java Enterprise.…”
Section: Static Analysis For Microservices-based Systemsmentioning
confidence: 99%
“…In our follow-up work [18] 3 , we intended for generalization and proposed that the AST is extended to be a superset across languages, which we call Language Agnostic AST (LAAST). Using LAAST, it is fairly simple to build or customize pattern matching agents to detect components or higher-level structures.…”
Section: Static Analysis For Microservices-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major challenge with static analysis is the code analysis language dependency and distribution. While the initial approach to address this challenge has been proposed [9], the tooling support is not yet available.…”
Section: Background and Related Workmentioning
confidence: 99%